Persepsi Masyarakat Terhadap Penyakit Rabies - I Made Kerta Duana Nida Ul Hasanat Retna Siwi Padmawati (Berita Kedokteran Masyarakat (BKM), 2011)
Background: Rabies is a viral disease that causes acute encephalitis (inflammation of the brain) in warm-blooded animals, and human. The rabies virus infects the central nervous system, ultimately causing disease in the brain and death. Rabies in Bali was firstly discovered in Badung District. Rabies was transferred by dog bite. Bali has enourmous dog population, the number reach approximately 540.000 animals or about 96 animals per square kilometer. Meanwhile, domesticated dog population only about 30 percent, the rest is wild dog that live on the street. Rabies in Bali need to be considered by all parties to change the mindset and the behaviour of keeping dog as pet, also efforts in solving of rabiesObjective: To recognizing the perception of Balinese people regarding rabies, preventing and solving efforts of rabies.Method: This research is a qualitative research using phenomenology approach. The data is collected by conducting deep interview technic and focus discussion group (FGD). The subject of the research consists of community with risk of rabies infection in Bali. The data is analysed by using constant comparative method, consists of four activity process; reduction, chategorisation, sintesisation, and interpretation.Result and Discussion: Dog domestication by Balinese community has been conducted for hundreds of year, passed on from one generation to the next, and no prohibition from religion or tribe regulation. Keeping dog at home then set them free will accelerate rabies infections to other dog and human. The high number of dog bite and victims of rabies has caused unsecurity in the community. This will also affect the changing pattern of medication of dog bites.Conclusion: The misperception about rabies was caused by the lack of information that people can get. The ineffectiveness of government program to combat rabies, such as vaccination, elimination, health promotion and community empowerment stimulate the spread of rabies throughout Bali. Some matters that need to be notified are the lack of people’s participation and ineffective illumination, also promoting effective implementation of vaccination and eliminating dog while still considering the culture value of local community.Keywords: perception, rabies, dog, health promotion